Design of porous structures for 3D printing - Lim, Nicholas Wei Sheng (2019)
Electrode efficiency is an emerging study for its catalytic properties in many electrochemical applications, from use in batteries and supercapacitors to electrolysis. In this report, focus is placed on the effect of effective electrode surface area on electrodes for the electrolysis process to obtain Hydrogen gas. First, the simulated models will be modelled in Solidworks and imported into Ansys CFX as an ACIS file. The recommended pore size will be evaluated by running a series of simulations of various strut geometries with decreasing pore sizes. The ideal pore size will be identified by the turning point in the graph plotted using Superficial velocity and Volume fraction values at which these values increase significantly. With these results, suggestions will be implemented onto several lattice structures and the simulation results compared to a control run. There were 3 strut geometries compared (square, pointed base triangle and flat base triangle). The triangles performed significantly better than square struts with the pointed base triangle performing the best of the three. With the identified ideal pore size and ideal strut geometry, two lattice structures were optimised, and simulations ran. The measured parameters showed significant performance improvements over the control runs.